The application of Shari’ah contract in Islamic financing guarantee schemes of Credit Guarantee Corporation (CGC) / Husniyati Ali, Badrul Hisham Kamaruddin and Ismail Ahmad - Ali, Husniyati; Kamaruddin, Badrul Hisham; Ahmad, Ismail (Universiti Teknologi MARA, Shah Alam, 2019)
Islamic financing is regarded as one of the financing alternatives that enterprises may utilize to fund their business. This financing type is characterized as free from riba and is based on illiquid assets which create real assets and inventories. The aim of this conceptual paper is to highlight the Shari’ah contract of al Kafalah that is used by Credit Guarantee Corporation (CGC) to attach to its Islamic financing guarantee scheme offered to business enterprises. Kafalah refers to an obligation to pay in the event the principal debtor is unable to honour his obligation. Through this Shari’ah contract, the CGC has indeed paved a new way of financing enterprises which are keen on having halal financing to fund their business activities. Most importantly, this addition of halal financing has accelerated the growth of Islamic finance in Malaysia.